Investigating chronic meningitis. Issue 5 (21st September 2009) - Syed, N; Saxena, A; Hartley, L
Abstract : Chronic meningitis is a syndrome characterised by persistent and progressive signs and symptoms of meningitis along with cerebrospinal fluid (CSF) pleocytosis and elevated protein that fail to improve over 4 weeks. A detailed and careful history and examination is required along with CSF parameters to guide a clinician towards the aetiology of the problem. Neuroimaging modalities have become a useful tool in the quest for a diagnosis in such cases. An interesting case is described in real time illustrating the process of making a diagnosis in chronic meningitis with an insight into investigations and subsequent management.